2005
DOI: 10.1590/s0104-42302005000500023
|View full text |Cite
|
Sign up to set email alerts
|

Índice de gravidade da doença renal, indicadores assistenciais e mortalidade em pacientes em hemodiálise

Abstract: The ESRD-SI is useful to assess the severity of comorbidities and to predict mortality in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
7
0
11
Order By: Relevance
“…CRF is a disease associated with many comorbidities, and these are determinants in the survival and morbidity of patients undergoing HD (22) . In this study, SAH and DM were found to be the prevalent comorbidities, followed by cardiovascular diseases, which is corroborated by other studies (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…CRF is a disease associated with many comorbidities, and these are determinants in the survival and morbidity of patients undergoing HD (22) . In this study, SAH and DM were found to be the prevalent comorbidities, followed by cardiovascular diseases, which is corroborated by other studies (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Time undergoing treatment is important in the worsening of comorbidities, and it was pointed out by several studies as a determining factor for survival of patients undergoing hemodialysis (8) .…”
Section: Discussionmentioning
confidence: 99%
“…24,27,43 This fact may be enhanced when there is a possibility of a transplant: the individual often does not assimilate the disease and the treatment to be submitted and appears the perspective a surgery in which he will have to receive an organ of another person, living or dead. 44 .…”
Section: Erro! Indicador Não Definidomentioning
confidence: 99%